Successful Ablation for Atrial Tachycardia Originated from Sinus Venosa with Tachycardia-Induced Cardiomyopathy - Sou Takenaka; Hideaki Sato; Mikio Yuhara; Takashi Uchiyama (Case Reports in Cardiology)
A 74-year-old male suffering from congestive heart failure with atrial tachycardia (AT) with 2 : 1 atrioventricular conduction was admitted to our hospital. After the therapy with diuretics and β-blocker, his rapid AT was still sustained. He took the catheter ablation for his AT. Postpacing interval mapping from entrainment and noncontact mapping system revealed the mechanism of his AT, originated from sinus venosa. His AT was successfully terminated and eliminated by radiofrequency catheter ablation. After the successful ablation, he has been free from any AT, and his cardiac function was also improved.